Amplification of poly(I:C)-induced interleukin-6 production in human bronchial epithelial cells by priming with interferon-γ - Norikazu Okuma; Masa-aki Ito; Tomoyoshi Shimizu; Atsuya Hasegawa; Shin’ya Ohmori; Kazuki Yoshida; Isao Matsuoka (Scientific Reports, 2023)
Abstract Proinflammatory cytokine interleukin (IL)-6 was associated with disease severity in patients with COVID-19. The mechanism underlying the excessive IL-6 production by SARS-Cov-2 infection remains unclear. Respiratory viruses initially infect nasal or bronchial epithelial cells that produce various inflammatory mediators. Here, we show that pretreatment of human bronchial epithelial cells (NCl-H292) with interferon (IFN)-γ (10 ng/mL) markedly increased IL-6 production induced by the toll-like receptor (TLR) 3 agonist poly(I:C) (1 µg/mL) from 0.4 ± 0.1 to 4.1 ± 0.4 ng/mL (n = 3, P < 0.01). A similar effect was observed in human alveolar A549 and primary bronchial epithelial cells. TLR3 knockdown using siRNA in NCl-H292 cells diminished the priming effects of IFN-γ on poly(I:C)-induced IL-6 production. Furthermore, the Janus kinase (JAK) inhibitor tofacitinib (1 µM) inhibited IFN-γ-induced upregulation of TLR3, and suppressed poly(I:C)-induced IL-6 production. Quantitative chromatin immunoprecipitation revealed that IFN-γ stimulated histone modifications at the IL-6 gene locus. Finally, IFN-γ priming significantly increased lung IL-6 mRNA and protein levels in poly(I:C)-administrated mice. Thus, priming bronchial epithelial cells with IFN-γ increases poly(I:C)-induced IL-6 production via JAK-dependent TLR3 upregulation and chromatin remodeling at the IL-6 gene locus. These mechanisms may be involved in severe respiratory inflammation following infection with RNA viruses.